Legality of use of drones - Slabá, Tereza (2016)
The thesis analyses the legality of the use of drones in warfare based on the examination of three specific case studies. Firstly the use of armed drones in Afghanistan 2001 and 2002, then Pakistan drone strikes ongoing since 2004 and lastly the Yemen case study. A developed legal framework is used to assess the legality of the use of drones. Furthermore, it briefly touches upon the aspects of morality and ethics of the use of the unmanned aerial vehicles in combat.